IMPLEMENTASI PEMBELAJARAN TIPE STAD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA - Ruslan Zaenudin (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2019)
The following article is "Implementation of STAD Type Learning to improve Activities and Student Learning Outcomes". The research background is due to the lack of activity of students in the teaching and learning process, lack of motivation to take part in learning, and unsatisfactory student learning outcomes. The method used is in the form of Cooperative Type STAD learning. The research location was conducted at MIN 3 Pangandaran. The study was conducted in three cycles. In the first cycle, some students are not familiar with the STAD Type Cooperative learning conditions. In the second cycle, students and teachers have begun to understand the implementation of STAD Type Cooperative learning and have shown satisfactory results. From the observation results, student activity increases. Whereas the daily test results showed an increase from an average of 5.48 on the first repeat daily test (before the use of STAD Cooperative Learning type) to an average of 6.53 on the second and second daily tests averaging 7.33 on the third daily test. (after the use of Cooperative Type STAD learning. From the implementation of Classroom Action Research, the first, second and third cycles it can be concluded that Cooperative Learning Type STAD can improve student learning outcomes and activities in Jurisprudence learning in class V MIN 3 Pangandaran.